Selection of a suitable microgrid to couple with an overloaded neighboring microgrid based on decision making - Bourbour, S.; Shahnia, Farhad; Ghosh, A. (2015)
It is expected that a microgrid (MG) can supply its local loads independently; however the load and generation intermittency may lead an MG to experience overloading. This problem can be mitigated by coupling the overloaded MG to another neighboring MG that has surplus power. It is a challenge to select a suitable MG within a distribution network composed of several islanded MGs, to be coupled to the overloaded MG. This paper presents a new decision-making-based method to select the suitable alternative. This selection is based on different criteria including the available surplus power, reliability, supply security, power loss, electricity cost and CO2 emissions in the alternative MGs. Moreover, the frequency and voltage deviation in the system of coupled MGs are considered in the selection. The performance of the developed method is evaluated within a cloud theory-based probabilistic analysis in MATLAB.